Disruption of the tumour-associated EMP3 enhances erythroid proliferation and causes the MAM-negative phenotype - Nicole Thornton (Nature Portfolio, 2020)
The molecular basis of the clinically important MAM blood group antigen present in most humans is unknown. We identify EMP3 as its encoding gene, establishing MAM as a new blood group system, and demonstrate the role of EMP3 in erythropoiesis through its interaction with the signalling molecule CD44.